Exploring new links between crystal plasticity models and high-energy X-ray diffraction microscopy. Issue 5 (October 2019) - Shade, Paul A.; Musinski, William D.; Obstalecki, Mark; Pagan, Darren C.; Beaudoin, Armand J.; Bernier, Joel V.; Turner, Todd J.
Highlights: Crystal plasticity model development requires targeted experimental validation. HEDM experiments provide new insights into microstructure dependent plasticity. Direct HEDM-simulation comparison offers a pathway for future development. Abstract: The advancement and transition of computational materials models requires corresponding developments in experimental methods to provide new phenomenological insights as well as quantification of model performance. In this article, we explore the natural links between crystal plasticity modeling and a suite of high-energy X-ray diffraction experimental techniques referred to as high-energy diffraction microscopy (HEDM). HEDM methods provide information such as the elastic strain state of individual grains and the distribution of crystallographic orientations. As a non-destructive characterization method, pairing HEDM with in situ mechanical testing enables tracking of material state evolution through quantitative measurements that may be directly compared to a simulation. We highlight some recent successes in this area and provide suggestions for future research.